Success factors in a reward and equity based crowdfunding campaign - Ferreira, Francisco Pedro Santos Miranda (2018)
As the world changes, financial sector changes with it, and alternative finance emerge. Crowdfunding is part of this evolution and its use is becoming more widespread day by day. As more entrepreneurs and organizations seek crowdfunding to fund their ventures, it becomes of uttermost importance to create a framework to help them to succeed raising finance. It is, therefore, the main goal of this thesis, to provide a valuable framework, a useful guide, to help entrepreneurs in the hard task of raising finance through crowdfunding, mainly those using equity crowdfunding. To accomplish the purposed goal, it is important to understand the underlying motivations of those investing in equity crowdfunding, in order to offer them what they seek and what motivates them. It is also vital, for those searching for financing, which kind of crowdfunding fits better with their goals and which one increases the likelihood of achieving them. Finally, is crucial to understand the specific success factors for a successful crowdfunding campaign. As an important problem for a successful crowdfunding or equity crowdfunding campaign is not the information available but rather its dispersion, this framework pretends to collect several information, from different sources, such as literature in the topic already existent, data collected from crowdfunding platforms, specialized people in the area and primary research, in one place to make it easier, for those searching for financing, through crowdfunding and equity crowdfunding, to achieve their goals.